Regression of the Flow Signal from the Neovascular Network in AMD Neovascular Membranes Treated with Faricimab - Maria Cristina Savastano; Emanuele Crincoli; Lisa Toto; Maria Oliva Grassi; Flavia Chiosi; Alfonso Savastano; Clara Rizzo; Rodolfo Mastropasqua; Francesco Boscia; Stanislao Rizzo (Diagnostics)
Objectives: To report the occurrence of the regression of the flow signal from the neovascular network in macular neovascularizations (MNVs), developing in the context of age-related macular degeneration (AMD), treated with faricimab in a treat-and-extend regimen. Methods: Eyes affected by AMD-related MNV and treated with faricimab intravitreal injections in a treat-and-extend (TE) regimen were consecutively retrospectively screened in five specialized retina centers. Changes in neovascular network characteristics during the course of the treatment were analyzed. The availability of high-quality optical coherence tomography angiography (OCTA) at the beginning of the treatment and at the regression of the MNV was necessary for inclusion. According to greatest linear diameter (GLD) changes during treatment, eyes were divided into three groups: a complete regression (CR) group, a partial remission (PR) group (a reduction of at least 50% of the GLD from baseline to last follow-up), and a stable group (stable/showing a reduction lower than 50% of the GLD from baseline to follow up). Results: One hundred and ten (110) eyes were included. The CR group was composed of 12 eyes (10.9%), while the PR group represented 60.9% of the study population. CR occurred after a mean of 6.0 ± 1.4 months, ranging from 4 to 8 months. Time to regression was significantly lower in eyes naïve to treatment before the study compared with the others (p = 0.022). A significantly lower baseline GLD was detected in the CR group (1292.2 ± 195.6 μm) compared with the PR group (1324.6 ± 135.6 μm) and the stable group (1412.5 ± 110.9 μm) (omnibus p = 0.003). Conclusions: Complete regression of the flow signal from the MNV neovascular network documented with OCTA may occur during TE regimens with faricimab. In treatment-naïve eyes, regression occurs earlier during the treatment.